Compounded with hemoglobin Port Phillip and ‐α4.2 or ‐‐SEA deletions were identified in Chinese population - Du, Li; Bao, Xiuqin; Qin, Danqing; Wang, Jicheng; Yao, Cuize; Liang, Jie; Chen, Jianhong; Yin, Aihua (Molecular genetics & genomic medicine, 2021)
Introduction Although over 1000 hemoglobin (Hb) variants were identified so far, Hb Port Phillip compound with α‐thalassemia deletion had no reported before. Methods Two patients and the associated families from Guangdong province in China were recruited. Hematological parameters were determined by blood routine examination and hemoglobin electrophoresis. Genotyping was performed by Gap‐PCR and Sanger sequencing. Results One patient was diagnosed as Hb Port Phillip, while her daughter was compounded with ‐α4.2 deletion, with normal Hb level (150 g/L), mean corpuscular volume (MCV) 108.4 fl and mean corpuscular hemoglobin (MCH) (30.5 pg). Another patient was diagnosed as compound Hb Port Phillip and ‐‐SEA deletion. This proband presented with more severe α‐thalassemia trait than the patient compounded with ‐α4.2 deletion, with hemoglobin 80 g/L, MCV 61.7 fl, and MCH 18.7 pg. Conclusion Here we first time identified two patients compound with Hb Port Phillip and ‐α4.2 and ‐‐SEA deletions, respectively, which had never been reported. Our study widens the genotypes of hemoglobinopathy and provides reference for genetic counselling and prenatal diagnosis in this population. Hemoglobin variants are a group of hereditary hemoglobin diseases and the phenotype ranges from asymptomatic to severe clinical manifestations. Hb Port Phillip was reported with decreased hemoglobin stability and presented as hypochromic polyglobulia microcytic red blood cells. In this study, we first time identified two probands compound with Hb Port Phillip and ‐α4.2 and ‐‐SEA deletions, respectively, and provided reference for genetic counselling and prenatal diagnosis in Chinese population.